Cap recovery technique and double-edge sign during small-incision lenticule extraction. Issue 9 (September 2021) - Carp, Glenn I.; Reinstein, Dan Z.; Stuart, Alastair; Vida, Ryan S.; Archer, Timothy J.; Finkel, Jake N.
Abstract : The cap recovery technique provides consistent and reliable identification of the cap interface when the lenticule interface is separated first, leaving the lenticule attached to the underside of the cap. Abstract : Purpose: To describe a new technique for identifying the upper (cap) interface during small-incision lenticule extraction (SMILE). If the lower interface is dissected first it can be challenging to locate the cap interface and complete the lenticule separation. Setting: London Vision Clinic, London, United Kingdom. Design: Retrospective analysis. Methods: The routine protocol was to open the primary small incision and separate the cap interface, followed by the lenticule interface. If the lenticule interface was dissected first, the modified Sinskey tip was inserted through the superior end of the incision, tangentially along the cap edge interface and then rotated anteriorly to engage the edge of the lenticule adherent to the underside of the cap. The Sinskey tip is then drawn inferiorly, creating a pocket of separation of the lenticule from the cap, enabling the dissection bulb and spatula to be used to dissect the upper interface. Results: A total of 629 consecutive eyes undergoing SMILE using the VisuMax femtosecond laser were included. The routine surgical protocol (cap interface first) was followed in 88% of eyes and the lenticule interface first in 12% of eyes. The lenticule was extracted successfully in all cases. Uncorrected distance visual acuity at the 1-day postoperative visit was 20/25 or better in 81% of the cap interface first group and 86% of the lenticule interface first group. Conclusions: The visual results using this cap recovery technique were equivalent to those when a routine SMILE dissection was performed. The technique allowed surgeons to rescue more challenging cases where identifying the different interfaces was difficult. This technique meant that separating the lenticule interface first should no longer be considered a complication of SMILE.